2022
DOI: 10.1007/s10344-022-01572-z
|View full text |Cite
|
Sign up to set email alerts
|

Usutu virus in blackbirds (Turdus merula) with clinical signs, a case study from northern Italy

Abstract: Usutu virus (USUV) is a mosquito-borne virus belonging to the family Flaviviridae, genus Flavivirus. Natural transmission cycle of USUV involves mosquitoes and birds, so humans and other mammals are considered incidental hosts. In this study, USUV infection was diagnosed in all wild blackbirds, collected from July to September 2018 in a wildlife recovery center in the province of Bologna, in the Emilia-Romagna region, northern Italy. All blackbirds showed neurological clinical signs, such as overturning, pedal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…Based on the experience of wild bird mortality caused by USUV in mainland Europe (e.g. 4 , 9 , 10 ), the syndromic surveillance categories generalised ill health and neurological disease were considered of particular interest as a potential signal of infection. However, USUV could not be excluded as a possible underlying cause for DIRs categorised as musculoskeletal disease, trauma, predation, drowning or tick parasitism, or where blackbirds were found dead with no observed clinical signs.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the experience of wild bird mortality caused by USUV in mainland Europe (e.g. 4 , 9 , 10 ), the syndromic surveillance categories generalised ill health and neurological disease were considered of particular interest as a potential signal of infection. However, USUV could not be excluded as a possible underlying cause for DIRs categorised as musculoskeletal disease, trauma, predation, drowning or tick parasitism, or where blackbirds were found dead with no observed clinical signs.…”
Section: Methodsmentioning
confidence: 99%
“…Assessing the causes of death of wild birds has been shown to be a useful practice to detect virus circulation [ 9 ] and should be maintained and encouraged also in the autumn–winter period, due to the importance of the health surveillance of these potentially zoonotic viruses. Most of the subjects had collision trauma but we cannot establish whether this was a consequence of the Flavivirus infection or a coincidental finding.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the subjects had collision trauma but we cannot establish whether this was a consequence of the Flavivirus infection or a coincidental finding. By undermining the functionality of the neural system, Flavivirus might increase the risk of bird collisions with the surrounding environment and anthropogenic elements (e.g., buildings and cars) [ 9 ]. Most of the positive subjects were in a good nutritional state (7/9-77.8%), which could suggest asymptomatic positivity or acute virosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested a possible sentinel role of the common blackbird in outbreaks of USUV infections, as the virus introduction in Europe was associated with increased mortality in this bird species in all the countries where outbreaks were recorded [7,30,34,35]. A possible explanation could be the weaker immune system of this species [36].…”
Section: Discussionmentioning
confidence: 99%